2018
DOI: 10.3390/ijms19082291
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Liver Steatosis in BAP31-Deficient Mice Burdened with Tunicamycin-Induced Endoplasmic Reticulum Stress

Abstract: Endoplasmic reticulum (ER) stress is highly associated with liver steatosis. B-cell receptor-associated protein 31 (BAP31) has been reported to be involved in ER homeostasis, and plays key roles in hepatic lipid metabolism in high-fat diet-induced obese mice. However, whether BAP31 modulates hepatic lipid metabolism via regulating ER stress is still uncertain. In this study, wild-type and liver-specific BAP31-depleted mice were administrated with ER stress activator of Tunicamycin, the markers of ER stress, li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 41 publications
1
22
0
Order By: Relevance
“…Another study with these mice reported the same effects upon tunicamycin treatment, as well as increased levels of ER-stress markers [175]. In Bap31-deficient mice, although not statistically significant, a trend toward increased p-eIF2a, ATF4, and CHOP signaling was observed [175]. Moreover, hepatocytes of these mice show increased lipogenic gene expression and SREBP1C expression, and activation of SREBP signaling.…”
Section: Metabolic Impact Of Alterations In Proteins Participating Inmentioning
confidence: 75%
See 3 more Smart Citations
“…Another study with these mice reported the same effects upon tunicamycin treatment, as well as increased levels of ER-stress markers [175]. In Bap31-deficient mice, although not statistically significant, a trend toward increased p-eIF2a, ATF4, and CHOP signaling was observed [175]. Moreover, hepatocytes of these mice show increased lipogenic gene expression and SREBP1C expression, and activation of SREBP signaling.…”
Section: Metabolic Impact Of Alterations In Proteins Participating Inmentioning
confidence: 75%
“…Bap31-deficient mice show enhanced body weight, increased food intake, and greater liver steatosis after exposure to a HFD [174]. Another study with these mice reported the same effects upon tunicamycin treatment, as well as increased levels of ER-stress markers [175]. In Bap31-deficient mice, although not statistically significant, a trend toward increased p-eIF2a, ATF4, and CHOP signaling was observed [175].…”
Section: Metabolic Impact Of Alterations In Proteins Participating Inmentioning
confidence: 99%
See 2 more Smart Citations
“…The protein levels of cyclin D1, cyclin E, CDK2, CDK4, Ki-67 and PCNA were decreased in shRNA-VCP-transfected cells [26]. Moreover, ER stress marker levels were increased in Bap31 knockout mice after tunicamycin injection compared with those in control mice [35]. The depletion of VCP by siRNA induces ER stress and the unfolded protein response (UPR) [36].…”
Section: Discussionmentioning
confidence: 95%